Swarming robots (B) - Pan, Ming En (2009)
This project is to demonstrate swarming behaviour by using a small group of two wheeled robots. The objective is to investigate the use of low cost robots with simple sensors and algorithms to accomplish a given task. This is achieved by using numerous robots working in a coordinated manner though wireless inter-robot communication.